2017
DOI: 10.15517/rbt.v65i4.27903
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variation of roadkills show mass mortality events for amphibians in a highly trafficked road adjacent to a national park, Costa Rica

Abstract: Abstract:Roads have detrimental impacts on wildlife populations around the world. Specifically, roads pose direct and indirect threats to wildlife by limiting dispersal movements or through vehicle-related mortality. The rate of wildlife mortality varies both in time and space depending on the landscape composition and the type and use of road infrastructure. The objective of this study was to investigate spatiotemporal variation of vertebrate mortality in a 4 km segment of the 34 national road, adjacent to Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
(67 reference statements)
0
24
0
2
Order By: Relevance
“…Clearly, this proximity condition is expected to exacerbate the negative effects roads exert on wildlife. For instance, an estimated number of 4709 vertebrates were killed by vehicles, particularly amphibians, in Carara National Park during a year period study (Arévalo et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, this proximity condition is expected to exacerbate the negative effects roads exert on wildlife. For instance, an estimated number of 4709 vertebrates were killed by vehicles, particularly amphibians, in Carara National Park during a year period study (Arévalo et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The Costa Rican road network is comprised of approximately 40 000 km of roads, of which about 10 000 km are paved (Transportation National Plan of Costa Rica, 2011). Although there have been some concerns about the effects of roads on wildlife mortality (Arévalo et al, 2017;Monge-Ná-jera, 1996;Pomareda, 2012;Rojas-Chacón, 2011); there are no studies regarding road proximity, volumes of traffic or the effect of noise in protected areas in Costa Rica, to our knowledge.…”
mentioning
confidence: 99%
“…Moreover, amphibians are one of the most threatened vertebrate groups (Stuart et al, 2004), with nearly 40% of living amphibian species in danger of extinction (IUCN, 2011). Amphibians have several unique life-history or behavioural traits, such as seasonal migrations (e.g., from overwintering sites to aquatic breeding sites; Orlowski, 2007;Semlitsch, 2008;Hartel et al, 2009;Andrews, Nanjappa & Riley, 2015), relatively slow movement (Carr & Fahrig, 2001;Puky, 2005;Garrah, 2012;Hamer, Langton & Lesbarrères, 2015), and the tendency to remain immobile in response to oncoming vehicles (Mazerolle, 2005;Rytwinski & Fahrig, 2012;Lima et al, 2015), which make them more prone to road-kill events than most other vertebrate species when crossing roads (Hels & Buchwald, 2001;Gryz & Krauze, 2008;Matos, Sillero & Argana, 2012;Alroy, 2015;Heigl et al, 2017).Additionally, because of their small body size, they are difficult for drivers to see, which increases the number of collision events (Andrews, Nanjappa & Riley, 2015;Arévalo et al, 2017). Hence, the extensive amounts of road mortality resulting from the pervasiveness of roads have prompted road planners and ecologists to implement mitigation measures to offset the negative effects that roads have on wildlife (Costa, Ascensao & Bager, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, although there are a number of studies on assessment of the influences on amphibians during certain traffic volume periods (Mazerolle, 2004;Sutherland, Dunning & Baker, 2010;Arévalo et al, 2017), few similar studies have been performed in China. For instance, Hels and Buchwald (2001) conducted a study on the peninsula of Djursland, where they examined the diurnal variations in the amphibian fraction of road kill and found that amphibian road mortality reached its highest peak after sunset, which may be attributable to their activity patterns.…”
Section: Introductionmentioning
confidence: 99%
“…After a 15-year hiatus, Costa Rican roadkill research revived in a variety of studies about which species were more affected, mortality rates and remediation options (e.g. Rojas, 2011;Araya-Gamboa & Salom-Pérez, 2013;Arévalo et al, 2017).…”
mentioning
confidence: 99%